Environments and physical activity in chronic diseases: Beyond associated factors - Muñoz-Rodríguez, Diana Isabel; Arango-Alzate, Catalina Maria; Segura-Cardona, Ángela Maria (Universidad y Salud, 2018)
Introduction: Chronic noncommunicable diseases are the major cause of morbidity and mortality. The most cost-effective strategy is the practice of physical activity but there is a direct relationship between the increase of these diseases with the high prevalence of physically inactive people. Objective: To collect the essential elements of chronic diseases in terms of impact and their negative effects and to show, within risk factors, physical inactivity as one of the key determinants in their emergence and the role of environments built on this unhealthy behavior. Materials and methods: A descriptive study was conducted through documentary review on the role of environments as determinants between physical inactivity and the development of chronic noncommunicable diseases. Results: The negative effects of chronic diseases are described as well as the factors that influence their appearance. Physical inactivity is highlighted as one of the determinants of chronic diseases. The empirical evidence suggests that the characteristics of the environment work as determinants in this behavior within the lifestyles. Conclusion: The environments where people inhabit are associated factors and determinants in the practice or not of physical activity and should be considered, beyond the individual factors, if there is the need to succeed in the prevention and control of noncommunicable diseases.